The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/hsr2.1149
|View full text |Cite
|
Sign up to set email alerts
|

Studying the prevalence of musculoskeletal pain among a sample of medical students in Damascus, Syria. A cross‐sectional study

Abstract: Background: A considerable number of medical students experience musculoskeletal pain (MSP) during their academic years. In this study, we seek to determine the prevalence of MSP, as well as its associated risk factors, among a sample of medical students at two major universities in Damascus, Syria.Methods: A cross-sectional study was conducted in two universities, with a total of 2009 medical students participating in filling-in the paper-based questionnaire. A modified version of the Standardized Nordic Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Also, muscle spasms or pain in the joints before menstruation, wearing heels, and other traditionally feminine behaviors can also contribute to WRMSDs. 12,13 Our findings indicate that doctors are twice as susceptible as nurses to developing WRMSDs (OR = 2.03). The number of nurses employed in the hospitals included in our study was 2250 (43%), whereas the number of doctors employed there was 2900 (57%); this is because our study was conducted in Syrian educational hospitals When the proportion of doctors to nurses is often greater, which led to doctors performing most of the nurses' duties.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Also, muscle spasms or pain in the joints before menstruation, wearing heels, and other traditionally feminine behaviors can also contribute to WRMSDs. 12,13 Our findings indicate that doctors are twice as susceptible as nurses to developing WRMSDs (OR = 2.03). The number of nurses employed in the hospitals included in our study was 2250 (43%), whereas the number of doctors employed there was 2900 (57%); this is because our study was conducted in Syrian educational hospitals When the proportion of doctors to nurses is often greater, which led to doctors performing most of the nurses' duties.…”
Section: Discussionmentioning
confidence: 73%
“…These factors put female therapists at a disadvantage, especially when it comes to lifting or moving weak patients, seeing several patients in 1 day, and carrying heavy equipment, which adds to the physical strain. Also, muscle spasms or pain in the joints before menstruation, wearing heels, and other traditionally feminine behaviors can also contribute to WRMSDs 12,13 . Our findings indicate that doctors are twice as susceptible as nurses to developing WRMSDs (OR = 2.03).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Musculoskeletal pain is pain in ligaments, tendons, muscles, or joints due to repetitive movements, awkward postures, or musculoskeletal disorders (Felemban et al 2021;Ogunlana et al 2021). According to the World Health Organization (WHO 2021), in a study conducted in 2019, it was found that musculoskeletal pain had affected about 1710 million people worldwide, having negative repercussions on their daily activities, hours of sleep and a significant decrease in their productivity (Alkhateeb et al 2020;Alrumi et al 2020;Torbey et al 2023). Likewise, according to the existing literature, several studies have shown that university students are no strangers to suffering from such pain.…”
Section: Introductionmentioning
confidence: 99%